Physical functions and gait performance in school-aged children born late preterm. (December 2021) - Ito, Yuji; Ito, Tadashi; Sugiura, Hideshi; Kidokoro, Hiroyuki; Sugiyama, Yuichiro; Mizusawa, Jun; Natsume, Jun; Noritake, Koji; Kato, Yuichi; Ochi, Nobuhiko
Abstract: Background: Children born late preterm (LP) have an increased risk of poor developmental motor outcomes. Aims: This study aimed to assess physical functions and gait performance in school-aged children born LP. Study design: Cross-sectional study. Subjects: Physical functions and gait performance were evaluated in 277 children aged 6–10 years born LP ( n = 22) and full-term (FT) ( n = 255). Outcome measures: Physical function tests consisted of five times sit-to-stand test (FTSST), one-leg standing time, and grip strength. FTSST was used to assess the functional muscle strength of the lower limbs and dynamic balance function. Gait performance tests included gait quality, spatiotemporal gait parameters, and gait variability. Clinical data, physical functions, and gait performance were compared between two groups. Furthermore, logistic regression analysis was performed to assess the association between all variables and LP birth. Results: In physical function tests, children born LP showed poorer FTSST than those born FT ( p = 0.039). No significant difference in gait performance tests were identified between the two groups. Logistic regression analysis of FTSST for LP (adjusted for age at assessment) revealed that FTSST was significantly associated with LP birth ( p = 0.004, odds ratio = 1.579, 95% confidence interval = 1.160–2.149). Conclusions: We demonstrated the physical functions and gait performance in school-aged children born LP. Our findings indicate that it is important to focus on the decreased functional muscle strength of the lower limbs and reduced dynamic balance function related to LP birth to improve functional mobility in children born LP. Highlights: Children born late preterm (LP) showed poorer five times sit-to-stand test (FTSST). No significant difference in gait performance was observed between LP and full-term. Logistic regression analysis revealed the association between FTSST and LP birth. FTSST is a useful measure for functional mobility in school-aged children born LP.